Self-Acceptance and Social Support as Predictors of Gratitude among Parents of Children with Special Needs.: Penerimaan Diri dan Dukungan Sosial sebagai Prediktor Kebersyukuran pada Orang Tua dari Anak Berkebutuhan Khusus - Lailatul Izzah; Eva Yuliza; Leviana Nur Fadhillah (Nathiqiyyah, 2026)
This study aims to examine the role self-acceptance and sosial support as predictors of gratitude among parents of children with special needs. This research employed a quantitative survey design. A total of 76 parents of children with special needs from a public special education school in Pekanbaru. Indoensia, werw selected using random sampling. Data were collected using standardized psychological scales measuring self-acceptance, social support, and gratitude. Statistical analysis was conducted using IBM SPSS version 20 for Windows to assess the predictive contribution of self-acceptance and social support to gratitude. The findings reealed that the levels of self-acceptance (97.36%), social support (86.84%), and gratitude (100%) were predominantly in the high category. Regression analysis indicated that self-acceptance and social support significantly predicted gratitude, with a contribution value of 0.207, meaning that both variables explained 20.7% of the variance in gratitude among parents of children with special needs. The study highlights the importance of strengthening internal psychological resources (self-acceptance) and external support systems (social support) to foster gratitude in parents raising children with special needs. However, the study is limited by its relatively small sample size and focus on a single institution, which may affect generalizability. Future research should include broader samples and additional psychosocial variables. This study contributes to the positive psychology literature by examining gratitude from both intrapersonal and interpersonal perspectives in the context of parenting children with special needs—an area that remains underexplored, particularly within Indonesian cultural settings.